Copper Incorporation in Organic‐Inorganic Hybrid Halide Perovskite Solar Cells. Issue 43 (21st November 2018) - Song, Zhen; Jiang, Yidong; Liu, Jiang; Pan, Qifa; Zuo, Wentao; Zhang, Xu; Liao, Cheng; Mei, Jun
Abstract: The organic‐inorganic hybrid halide perovskite solar cell with excellent photovoltaic performance has been considered a promising device in photovoltaic field. By element substitution in perovskites, the crystal structure and properties of materials can be altered. Herein, two copper‐based compounds are used as additives in perovskites, which affect the crystallization process of perovskite films, and modify the photoelectric properties of perovskite materials. It is found that an appropriate addition of copper (Cu) ions could not only reduce the perovskite phase transition temperature, promote the formation of black perovskite phase, but also improve the crystallization and absorbance of perovskites. Excessive Cu incorporation leads to significant loss of device performance. The appropriate concentration of Cu ions in perovskite absorber for high efficiency solar cell is considered to be ∼0.1 mol% from a number of experimental results, which contributes to a remarkable stability of the device with only 2% power conversion efficiency loss after 170 h. This study is conducive to the comprehensive understanding of the effect of ions doping in perovskite materials. Abstract : The effect of the incorporation of Cu ions on crystalline, electrical and optical properties of perovskites has been investigated.